Analysis of Leadership Crisis Factors in Islamic Educational Institutions (Case Study at MAS Al-Washliyah Tanjung Tiram) - Cahaya, Cahaya; Rusdi, Muhammad; Damanik, Muhammad Zein (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
MAS Al-Washliyah Tanjung Tiram, a long-established Islamic institution in Batu Bara Regency, is currently experiencing a period of transition in its leadership structure. The crisis in leadership is the result of a complex interplay of internal and external factors. In order to address this crisis, it is necessary to implement strategic measures, including improvements in leadership competencies, enhancements in communication, and adaptations to external changes. The objective of this article is to examine the internal and external factors that have contributed to the leadership crisis at MAS Al-Washliyah Tanjung Tiram. A comprehensive analysis is presented. The research employs a qualitative design with a case study approach. The data were collected through a combination of in-depth interviews, participative observation, and document analysis. The findings revealed that internal factors, including ineffective communication, a lack of innovation, resource management challenges, and inadequate staff development, were contributing to the crisis. From an external perspective, the crisis was precipitated by shifts in government policy, economic pressures, competition from other institutions, and technological advancements.